Reduction of extrinsic tooth stain by a toothpaste containing 10% high cleaning silica, 0.5% sodium phytate and 0.5% sodium pyrophosphate: an 8-week randomised clinical trial - Hongchun Liu; Jiazhen Tu (BMC, 2021)
Abstract Objective To assess the effects for controlling extrinsic tooth stain of a whitening toothpaste containing 10% high cleaning silica, 0.5% sodium phytate and 0.5% sodium pyrophosphate, in comparison with a negative control toothpaste. Methods A total of 86 adults who met with the inclusion and exclusion criteria were invited to take part in the study. They were distributed into test and control groups randomly. At baseline, 4 weeks and 8 weeks, the same examiner provided the clinical examinations, including evaluations of oral soft and hard tissues and measurements of tooth stain of the anterior teeth using the Lobene Stain Index. Adverse events and any changes in general health conditions of the patients were monitored. Results When the study was completed, comparisons between patients in test and control groups yielded statistically significant differences in Lobene stain adjusted mean area score [0.83 (0.05) vs. 1.13 (0.05)], Lobene stain adjusted mean intensity score [0.99 (0.06) vs. 1.32 (0.06)] and Lobene stain adjusted mean composite score [1.45 (0.13) vs. 2.50 (0.13)] (All, P < 0.001). Patients in the test group exhibited reductions of 26.55%, 25% and 42%, respectively in Lobene stain area, intensity and composite scores, relative to patients in the control group. Comparisons within groups showed that all three Lobene scores at 8 weeks in both groups were lower than those at baseline (All, P < 0.001). Conclusion This study demonstrates that 8-week use of a toothpaste containing 10% high cleaning silica, 0.5% sodium phytate and 0.5% sodium pyrophosphate can effectively reduce extrinsic tooth stain. Trial registration NCT04238429 (before enrollment of the first participant). Data register: March 4, 2018.